Relationships between core strength, dynamic balance and knee valgus during single leg squat in male junior athletes - Affandi, Nor Fatinah; Mail, Mohamad Saufi Zuhan; Azhar, Norain Mohd; Shaharudin, Shazlin (Relationships between core strength, dynamic balance and knee valgus during single leg squat in male junior athletes, 2018)
a stable position while performing a task (Winter et al. 1990). On fields, athletes are always exposed to situations where the body balance is dynamically challenged while performing movements such as walking, running, stepping and jumping (Hrysomallis et al. 2006). For example, a dynamically balanced position in soccer can be perturbed either by the opponent or by the player themselves while passing a ball or while changing directions to avoid an opponent (Bhat & Moiz 2013). According to Hrysomallis (2011), balance ability has a significant effect on athletic performance. Additionally, poor balance has been associated with an increased risk of ankle injury in a number of sports (Hrysomallis 2007).